2018
DOI: 10.1002/ehf2.12262
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure: a weak link in CHA2DS2‐VASc

Abstract: AimsIn atrial fibrillation, stroke risk is assessed by the CHA2DS2‐VASc score. Heart failure is included in CHA2DS2‐VASc, but the rationale is uncertain. Our objective was to test if heart failure is a risk factor for stroke, independent of other risk factors in CHA2DS2‐VASc.Methods and resultsWe studied 300 839 patients with atrial fibrillation in the Swedish Patient Register 2005–11. Three definitions of heart failure were used in order to assess the robustness of the results. In the main analysis, heart fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…The clinical diagnostic component of the definition, evidence of HF, may be unreliable due to difficulty differentiating HF from lung or pulmonary vascular diseases. As clinical diagnoses are open to interpretation, some studies define CHF based on International Classification of Diseases (ICD) codes [5] while others including textbooks [6] do not specify clear criteria, leading to the need for a less ambiguous definition for CHF in the CHA 2 DS 2 -VASc scheme. A Meta-analysis demonstrated that out of 12 studies that define CHF as clinical heart failure, only 3 showed an association between CHF and the occurrence of stroke in patients with AF [4].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical diagnostic component of the definition, evidence of HF, may be unreliable due to difficulty differentiating HF from lung or pulmonary vascular diseases. As clinical diagnoses are open to interpretation, some studies define CHF based on International Classification of Diseases (ICD) codes [5] while others including textbooks [6] do not specify clear criteria, leading to the need for a less ambiguous definition for CHF in the CHA 2 DS 2 -VASc scheme. A Meta-analysis demonstrated that out of 12 studies that define CHF as clinical heart failure, only 3 showed an association between CHF and the occurrence of stroke in patients with AF [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, these above-mentioned two scoring systems do not take into account other potential risk factors, such as renal function impairment, rheumatoid arthritis, obesity or smoking, nor do they consider clinically accessible laboratory indicators, imaging values and other parameters [ 11 , 12 ]. Friberg et al [ 13 ] have shown that clinically diagnosed heart failure does not increase rates of stroke in AF patients. Other studies have shown that left atrial enlargement and low-density lipoprotein cholesterol (LDL-C) are clinically easy-to-obtain indicators for risk stratification of thromboembolism events in patients with AF [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the abovementioned two scoring systems do not take into account other potential risk factors, such as renal function impairment, rheumatoid arthritis, obesity or smoking, as well as clinically accessible laboratory indicators, imaging values and other parameters [4,5]. Friberg et al [6] have shown that clinically diagnosed heart failure is not an independent risk factor for stroke in AF patients. Previous studies have shown that left atrial enlargement and low-density lipoprotein cholesterol (LDL-C) are clinically easy-to-obtain indicators for risk strati cation of thromboembolism events in patients with AF [7][8][9].…”
Section: Introductionmentioning
confidence: 99%